Istana dan Pendidikan Islam: Ditinjau dari Perspektif Sejarah Sosial Pendidikan Islam - Siti Ropiqah; Aidul Azhari Harahap; Erawadi (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2024)
The history of Islam and Islamic educational institutions have been closely intertwined since ancient times to the present day. They have a significant connection in the social history of Islamic education, starting from the influence of Islamic kingdoms and various influential scholars in improving the quality and dissemination of Islamic education in various regions under their leadership. One of the policies in the past was the establishment of an Islamic educational institution by the kingdom (palace) for the education of royal descendants, which did not restrict access for the public to pursue education there. This research was conducted using the library research method, resulting in findings that contributed to knowledge and insights related to the addressed issues. The implementation of education for royal descendants became one form of more formal institutional institutions with a more directed educational curriculum, giving rise to Islamic educational institutions and the development of Islamic educational institutions. This represents one form of implementing the educational process within palace institutions, especially concerning Islamic education. However, there was a dichotomy in the implementation of the educational process considered as elite educational institutions within the Islamic Kingdom Palace at that time, giving rise to various terms for its educators such as